45 + 6| x - 56 | = 105
6 | x - 56 | = 105 - 45
6 | x - 56 | = 60
| x - 56 | = 60 : 6
| x - 56 | = 10
\(\Rightarrow\orbr{\begin{cases}x-56=10\\x-56=-10\end{cases}\Rightarrow\orbr{\begin{cases}x=66\\x=46\end{cases}}}\)
45+6./x-56/=105
=6./x-56/=105-45
=6./x-56/=60
=/x-56/=60:6
=/x-56/=10
=>x-56=10
x-56=-10
=>x=10+56
x=(-10)+56
=>x=66
x=46
\(45+6\left|x-56\right|=105\)
\(\Leftrightarrow6\left|x-56\right|=60\)
\(\Leftrightarrow\left|x-56\right|=10\)
\(\Leftrightarrow\orbr{\begin{cases}x-56=10\\x-56=-10\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=66\\x=46\end{cases}}\)